Application of the Fixed Asset Depreciation Method and its Impact on the Performance of Fixed Asset Reports at the One Stop Integrated Service and Investment Service - Siti Nur Widya Astuti; Zahri Fadli; Minasari Nasution (Sean Institute, 2025)
The aim of the company is basically to ensure that the company's operations continue to obtain optimal profits on the investment invested by the shareholders or owners in the company. Application of depreciation charges for fixed assets, using a depreciation method that is in accordance with government accounting standards. Asset depreciation method at the One Stop Integrated Services and Investment Service to calculate fixed asset depreciation expenses. The depreciation expense will result in a decrease in fixed assets and government equity on the balance sheet of the financial statements. The purpose of this research is to determine the application of the fixed asset depreciation method and its impact on the performance of the Fixed Asset Report used by the One Stop Integrated Services and Investment Service. The analytical method used is the descriptive method. The data collection technique used is a documentation study which is carried out by taking the necessary data and studying and analyzing it. Based on the research results, it shows that the calculation method for depreciation of fixed assets is appropriate according to Financial Accounting Standards (SAK) No. 17 of 2008 by determining the amount that can be depreciated first. The depreciation method used and to determine the economic useful life of an asset being depreciated.